Only learned to read in form 2, Ali, a Plantation Manager from Sabah, successfully earns his degree - Nur Hartini, Mohd Hatta (UMPSA, 2024)
GAMBANG, 29 October 2024 – Only learning to read when he was in Form Two, Ali Asman@Edit Jailani, 49, was often the target of ridicule by his friends and teachers.